BENTUK PENYAJIAN GEBANE DALAM UPACARA PERKAWINAN DI KAMPUNG PULAU KECAMATAN RENGAT RIAU - Devika Duri; Marzam Marzam; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2013)
Abstract This research was aimed at investigating and describing Gebane in a wedding ceremony. This research was a qualitative one. The findings have explained Gebane as a music art which uses Gebane as a membranophone music instrument to assisst songs of which lyrics found in Bezanggi (Al-Barzanji). Gebane in a wedding ceremony in Kampung Pulau is a kind of music ansambel in Berandam, Khatam Quran, Cecah Inai, Hari Langsung (to carry the brides and grooms to their houses). The songs lyrics are Ushalli and Annal. The elements which are related one another in the form of an art show include the instrument players, costumes, music instruments, time, place, and the audience. Kata Kunci: Bentuk Penyajian, Gebane, Upacara Perkawinan, Kampung Pulau